Salvianolic acid B attenuates membranous nephropathy by activating renal autophagy via microRNA-145-5p/phosphatidylinositol 3-kinase/AKT pathway. Issue 5 (2nd May 2022) - Chen, Junqi; Hu, Qinghong; Luo, Yini; Luo, Lina; Lin, Hua; Chen, Dandan; Xu, Yuan; Liu, Bihao; He, Yu; Liang, Chunling; Liu, Yaoyu; Zhou, Jiuyao; et al.
ABSTRACT: The abnormal proliferation and inflammatory response of the mesangial cells play a crucial role in the progression of membranous nephropathy (MN). Herein, this study aimed to investigate the therapeutic effect of Salvianolic acid B (SalB) on MN-induced mesangial abnormalities and its underlying mechanisms. MN models were established in cationic bovine serum albumin-induced Sprague-Dawley rats and lipopolysaccharide-induced human mesangial cells (HMCs). Following SalB and microRNA-145-5p antagomir treatment, kidney function was investigated by 24-hours urine protein, serum creatinine, and blood urea nitrogen. Pathological changes of kidney were investigated by Periodic acid Schiff staining. CD68 and IgG were detected by immunofluorescence in glomerulus. Mesangial autophagosomes were observed by transmission electron microscope. MicroRNA-145-5p inhibitor, mimic, LY294002, and SalB were used to treat with HMCs. In kidney and HMCs, IL-1 β, IL-2, IL-6, TNF- α and microRNA-145-5p was detected by quantitative real-time PCR. Phosphatidylinositol 3-kinase (PI3K), phosphorylated AKT, AKT, beclin1, and microtubule-associated protein light chain 3 (LC3) levels were detected by Western blot. HMCs proliferation and cycle were detected by Cell Counting Kit-8 and flow cytometry. LC3 were detected by LC3-dual-fluorescent adenovirus in HMCs. Our results showed that SalB significantly ameliorated kidney function and pathological changes. Furthermore, it significantly alleviated proliferation, inflammation and activated autophagy in mesangial cells. Moreover, microRNA-145-5p antagomir accentuated MN while microRNA-145-5p inhibitor and LY294002 encouraged proliferation and inflammation through PI3K/AKT pathway in HMCs. Collectively, our study demonstrated that SalB activated renal autophagy to reduce cell proliferation and inflammation of MN, which was mediated by microRNA-145-5p to inhibit PI3K/AKT pathway, and ultimately attenuated MN. GRAPHICAL ABSTRACT: uf0001